Prognostic impact of micromegakaryocytes in primary myelodysplastic syndromes. Issue 5 (16th April 2022) - Saumell, Sílvia; Fernández-Serrano, Miranda; Mesa, Alba; López-Cadenas, Félix; Arenillas, Leonor; Alfonso, Ana; Montoro, Maria Julia; Molero, Antonieta; Leoz, Pilar; Riego, Victoria; Gallur, Laura; Salamero, Olga; et al.
Abstract: Micromegakaryocytes (microMKs) are considered a myelodysplastic feature of myeloid neoplasms in adults, with an adverse prognosis connotation. However, this notion in MDS has not been well proved. In our cohort of 287 MDS, patients with microMKs showed lower overall survival (OS) (HR, 2.12; 95% CI, 1.47–3.06; p  = 0.000036) and higher risk of acute myeloid leukemia (AML) evolution (HR, 4.8; 95% CI, 2.9–11.01; p  = 0.00021). Results were validated with an independent cohort. In multivariate analysis, the presence of microMKs maintained its independent association with OS (HR, 1.54, 95% CI, 1.13–2.1, p  = 0.0059) and AML transformation (HR, 2.28, 95% CI, 1.2–4.4, p  = 0.014). Moreover, by adding 1 point to the IPSS-R score in patients with microMKs, we improved the IPSS-R accuracy. Interestingly, adding that 1-point, 29% of intermediate IPSS-R risk group patients were upgraded to the high-risk group. In summary, we confirmed that the presence of microMKs implies worse outcomes in MDS and suggested a modification improving IPSS-R.